Transient activation of YAP/TAZ confers resistance to morusin-induced apoptosis - Hoyeon Lee; Sang Woo Cho; Hyo Sun Cha; Kun Tae; Cheol Yong Choi (BMC Molecular and Cell Biology, 2025)
Abstract Background The Hippo signaling pathway involves a kinase cascade that controls phosphorylation of the effector proteins YAP and TAZ, leading to regulation of cell growth, tissue homeostasis, and apoptosis. Morusin, a compound extracted from Morus alba, has shown potential in cancer therapy by targeting multiple signaling pathways, including the PI3K/Akt/mTOR, JAK/STAT, MAPK/ERK, and apoptosis pathways. This study explores the effects of morusin on YAP activation and its implications for apoptosis resistance. Results Our investigation revealed that morusin induces transient YAP activation, characterized by the dephosphorylation of YAP at S127 and nuclear localization, followed by gradual rephosphorylation in multiple cancer cells. Notably, this activation occurs independently of the canonical Hippo pathway and involves the LATS1/2, MINK1, and MAPK pathways during the YAP inactivation stage. Furthermore, morusin-induced stress granule formation was significantly impaired in YAP/TAZ-depleted cells, suggesting a role in apoptosis resistance. Additionally, the expression of constitutively active MINK1 maintained YAP activation and reduced apoptosis, indicating that prolonged YAP activation can enhance resistance to cell death. Conclusions These findings suggest that YAP/TAZ are crucial in resistance to morusin-induced apoptosis, and targeting YAP/TAZ could enhance the anti-cancer efficacy of morusin. Our study provides new insights into the molecular mechanisms of morusin, highlighting potential therapeutic strategies against cancer by disrupting apoptosis resistance.